2017
DOI: 10.1002/smtd.201700102
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Peroxide Dihydrate or Sodium Superoxide: The Importance of the Cell Configuration for Sodium–Oxygen Batteries

Abstract: In sodium–oxygen (Na–O2) batteries, multiple discharge products have been observed by different research groups. Given the fact that different materials, gas supplies, and cell configurations are used by different groups, it is a great challenge to draw a clear conclusion on the formation of the different products. Here, two different cell setups are used to investigate the cell chemistries of Na–O2 batteries. With the same materials and gas supplies, a peroxide‐based product is observed in a glass chamber cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…[33] The second area where the sodium superoxide (NaO 2 )b and should appear is around 1156 cm À1 ,a nd this is not clearly detected.T herefore, the Ramans pectra corresponding to the discharge products for CNF-140a nd CNF-240 cannotc orroborate the generation of NaO 2 . However,t he peak is more prominent in the case of CNF-240, whereas only as mall peak can be seen in CNF-140.…”
Section: The Nature Of Discharge Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] The second area where the sodium superoxide (NaO 2 )b and should appear is around 1156 cm À1 ,a nd this is not clearly detected.T herefore, the Ramans pectra corresponding to the discharge products for CNF-140a nd CNF-240 cannotc orroborate the generation of NaO 2 . However,t he peak is more prominent in the case of CNF-240, whereas only as mall peak can be seen in CNF-140.…”
Section: The Nature Of Discharge Productsmentioning
confidence: 99%
“…However,t he peak is more prominent in the case of CNF-240, whereas only as mall peak can be seen in CNF-140. [33] The second area where the sodium superoxide (NaO 2 )b and should appear is around 1156 cm À1 ,a nd this is not clearly detected.T herefore, the Ramans pectra corresponding to the discharge products for CNF-140a nd CNF-240 cannotc orroborate the generation of NaO 2 .…”
Section: The Nature Of Discharge Productsmentioning
confidence: 99%
“…Therefore, results tend to vary from lab to lab. For example, a case study of two different cells revealed consistently different discharge products . In the assembly, all materials and electrolytes were identical between the two cells and exhibited the same water content.…”
Section: Sodium‐oxygen Batteriesmentioning
confidence: 99%
“…In the assembly, all materials and electrolytes were identical between the two cells and exhibited the same water content. In spite of this, one cell produced exclusively NaO 2 and the other produced Na 2 O 2 ⋅ 2 H 2 O . In order to improve reproducibility of results within the field we recommend a full cell design be included in the supporting information of the manuscript, along with the part numbers of any commercial parts used in fabrication.…”
Section: Sodium‐oxygen Batteriesmentioning
confidence: 99%
See 1 more Smart Citation